Réponses

Meilleure réponse !
2014-04-30T14:49:29+02:00
Salut :)

C = 5 - 3 * \frac{4}{9}+11 :  (\frac{-3}{2} )

C = 5 -  \frac{12}{9}+11 *  (\frac{-2}{3} )

C = 5 -  \frac{4}{3} + \frac{-22}{3}

C =  \frac{15}{3} -  \frac{4}{3} +  \frac{-22}{3}

C =  \frac{11}{3} -  \frac{22}{3}

C =  \frac{-11}{3}

J'espère t'avoir aidé(e) ! :)
Tu m'as beaucoup aidée , Merci beaucoup :D
Je t'en prie :)
2014-04-30T14:50:46+02:00
C =  5 - 3 x 4/9 + 11 / ( - 3/2 )
C = 5 - 12/9 + 11 x -2/3
C = 5 - 12/9 - 22/3
C = 5 x 9 / 1 x 9 - 12/9 - 22 x 3 / 3 x 3
C = 45/9 - 12/9 - 66/9
C = - 78/9 + 45/9
C = 33/9
C = 3 x 11 / 3 x 3
C = 11/3